The relationship between visit time management and patient's family satisfaction in the intensive care unit - Yuni Sudaryanto; Jebul Suroso (Proceedings Series on Health & Medical Sciences, 2020)
The Intensive Care Unit is an independent hospital part (an installation under the service director) with special staff and equipment for the observation, treatment and therapy of patients who suffer from life-threatening diseases, injuries or complications. Or potentially life-threatening. The policy of Intensive Care Unit by limiting the visiting times aims to maximize the care for patients with critical conditions. The satisfaction of the patient family is at the center point recognized as a measure of the quality of care services in the Intensive Care Unit. The purpose of this study was to determine the relationship between visiting time management and the satisfcation of the patient family It used a descriptive quantitative method, a correlation study with a cross sectional design. The sampling technique was total sampling with the respondents of the families, 40 respondents. They were then analyzed using Spearman Rank correlation statistical technique. The results of the Spearman rank analysis gave a p value of 0.044 <0.05, meaning there is a significant relationship between visiting-time management and the satisfaction of family patients.In conclusion he management of visiting-time can be an influential factor in determining the satisfaction of the patient family over the hospital services.